Development of gambling disorder after bariatric surgery: a call for research - Abdul Rahim, Yassir; Fernandez-Aranda, Fernando; Jimenez-Murcia, Susana; Håkansson, Anders (Frontiers in Public Health, 2023)
The relationship between bariatric surgery and alcohol use disorder (AUD) suggests that there may be a parallel connection between bariatric surgery and gambling disorder (GD), although this has never been researched before. Here, we describe observations suggesting that patients undergoing bariatric surgery may develop gambling disorders after surgery. Obese, older adults, and women may be at particular risk of developing GD because of their higher susceptibility to somatic comorbidities. We call for research addressing factors affecting the development of GD in patients undergoing bariatric surgery and how this could be prevented.